EVALUATION OF THE QUALITY OF USING PUBLIC TRANSPORT - N. B. Shanazarova (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, the development of the transport sector of our country is considered the most important and urgent requirement of the time, so it is necessary to study the experience and methods of advanced foreign countries in the development of the transport sector and apply them in the transport sector.